Some Results on Fixed Sets and Kernel Sets of Permuting \(n\)-\((f ,g)\)-derivation of Lattices - Chotchaya, Pongsatorn; Leerawat, Utsanee (Communications in Mathematics and Applications, 2022)
In this paper, we introduce a multivariate fixed set, a partial fixed set, a multivariate kernel set and a partial kernel set of permuting \(n\)-\((f , g)\)-derivation in lattices, and investigate some related properties. We also give some conditions under which these sets are sublattices and ideals.